Legitimation of value practices, value texts, and core values at public authorities. Issue 4 (August 2019) - Björkvall, Anders; Höög, Catharina Nyström
A large number of Swedish public authorities produce 'platform of values' texts that present core values. This article presents a study of how such texts and practices, including the core values they revolve around, are legitimized. Using Van Leeuwen's legitimation framework, three different data sets are analysed: 47 'platform of values' texts, a focus group discussion with seven senior HR officers, and a quantitative questionnaire study answered by civil servants at three public authorities. The analysis shows how the existence of 'platform of values' texts and practices is legitimized through rationalizations, above all by describing the texts as concrete means for reaching specific ends and, with regard to the choice of core values, through a custom-conformity type of authority. Thus, this article addresses discursive transformations of contemporary organizations with a particular focus on available discursive space for critical thinking in the wake of New Public Management and related developments.